The Relation of The Duration of Work in Dentists With Postural Problems, Range of Motion and Pain - Tekin, Demet; Koksal, Mesut (Bezmialem Vakif Univ, 2020)
Objective: The aim of this study is to determine the relationship between cervical and lumbar range of motions, pain and postural problems with the time spent in the occupation in dentists. Methods: A total of 56 dentists (27 males, 29 females), participated in this research as a volunteer (age=29.55 +/- 9.5 years). Firstly, the participants were divided into 3 groups according to the working years in their life and the time spent at unit during the day; they were also divided into 2 groups according to the intermittent or uninterrupted working conditions during the day. Cervical and lumbar joint range of motions were measured to determine limitations. The McGill pain scale survey was used to evaluate the pain. Kruskal Wallis and Mann-Whitney U tests with a posthoc Bonferroni test were used for all statistical analyses. Results: It was seen that the cervical and lumbar joint range of motions decreased, and the postural deformities in the spine and knee were observed and the level of pain increased significantly in comparatively to the excess of the time spent in the profession. However, in the analysis according to the time spent at the unit during the day, only the decrease in the range of motion of the regions was determined with the increase of the time spent at the unit during the day. Conclusion: With the increase in the working years in the dentists, it was revealed that the limitation of the range of motion increased and posture disorders and pain were formed. It is thought that all these problems will be caused by working in non-ergonomic environments for a long time. In this respect, it is important to include experts in the field of physiotherapy in the courses given under the name of preventive medicine. As a result, it can be said that the health problems encountered with the increase in time spent in the profession have increased.
koksal, mesut/0000-0002-2998-8222
Keywords: Pain; Dentists; Range Of Motion; Posture; Diş Hekimliği; Sağlık Bilimleri Ve Hizmetleri